« La durabilité forte : enjeux épistémologiques et politiques, de l’économie écologique aux autres sciences sociales » - Valérie Boisvert; Leslie Carnoye; Rémy Petitimbert (Développement Durable et Territoires)
The notion of "strong sustainability" is being reassessed in different disciplines of the humanities and social sciences such as history (Quenet, 2016), geography (Chartier, 2016), but also ethics and political science. It obviously raises important epistemological questions about the integration of environmental issues into social sciences (Blanc et al., 2017). However, the distinction between "weak" and "strong" sustainability first emerged in ecological economics in the mid-1990s. Strong sustainability immediately became part of the interplay of actors and conflicts of legitimacy that still weigh on its heuristic scope, as well as on its ability to nurture the plurality of representations of social relations with the environment.